DIPLOMASI PUBLIK TIONGKOK TERHADAP INDONESIA MELALUI UNSUR BUDAYA DALAM GAME GENSHIN IMPACT PERIODE TAHUN 2020-2021 - Mohammad Rizky Sulistio Putra (2024)
This study aims to analyze the role of China's public diplomacy towards Indonesia as viewed through cultural elements in the Genshin Impact game for the 2020-2021 period. In this study, researchers try to analyze how Genshin Impact applies cultural elements in China and how the Indonesian people respond to these diplomacy efforts. The research method used in this research is a qualitative method using a literature study approach. The data used consists of primary and secondary sources, including books, documents, archives, journals, articles and reports in the form of facts and other literature such as internet websites that can be accessed to support this research and provide a broader understanding of this topic. The results showed the attractiveness and popularity of Genshin Impact which was responded very enthusiastically by the Indonesian people. Through public diplomacy in this Genshin Impact game, it can change the bad image of China for the better in Indonesian society. With this high appeal, it has increased high enthusiasm among game players in Indonesia so that China can realize its public diplomacy.